2017
DOI: 10.1016/j.jes.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PFAAs in American alligators part 1: Concentrations in alligators harvested for consumption during South Carolina public hunts

Abstract: Environmental contamination resulting from the production or release of harmful chemicals can lead to negative consequences for wildlife and human health. Perfluorinated alkyl acids (PFAAs) were historically produced as protective coatings for many household items and currently persist in the environment, wildlife, and humans. PFAAs have been linked to immune suppression, endocrine disruption, and developmental toxicity in wildlife and laboratory studies. This study examines the American alligator, Alligator m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The life history characteristics of the alligator make it an attractive species for use as a sentinel, specifically their long-life spans, high site fidelity, varied diet, and their ability to live in proximity to humans (Wilkinson et al, 2016). Throughout the southeastern U.S. alligators are consumed as large game via recreational hunting and are a direct source of toxic element exposure to humans locally (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017). The locations sampled in this study are unique in that there are ongoing alligator monitoring programs in place which makes samples accessible for temporal studies, and the sites in Florida allow recreational hunting of alligators (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The life history characteristics of the alligator make it an attractive species for use as a sentinel, specifically their long-life spans, high site fidelity, varied diet, and their ability to live in proximity to humans (Wilkinson et al, 2016). Throughout the southeastern U.S. alligators are consumed as large game via recreational hunting and are a direct source of toxic element exposure to humans locally (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017). The locations sampled in this study are unique in that there are ongoing alligator monitoring programs in place which makes samples accessible for temporal studies, and the sites in Florida allow recreational hunting of alligators (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the southeastern U.S. alligators are consumed as large game via recreational hunting and are a direct source of toxic element exposure to humans locally (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017). The locations sampled in this study are unique in that there are ongoing alligator monitoring programs in place which makes samples accessible for temporal studies, and the sites in Florida allow recreational hunting of alligators (FFWCC, 2015; Tipton et al, 2017a, 2017b; Smith et al, 2017). To determine how the alligator can best be utilized as a sentinel species for local trace element exposure and to understand the exposure the alligators in this study experience relative to what is known for exposure and outcomes, the measurements in this study are evaluated by comparison to existing wildlife and human data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish exposed to PFNA alone were shown to have reproductive-related health effects (Zhang et al, 2016). There were five PFAAs (PFDA, PFUnA, PFDoA, PFHxS and PFOS; Tipton et al, accompanying paper) routinely detected in alligator meat from SC. Previous studies have reported similar results with a variety of PFAAs detected in wildlife (Ye et al, 2008; Reiner and Place, 2015; Bangma et al, 2017; Christie et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…PFAAs were analyzed using liquid chromatography tandem mass spectrometry (LC–MS/MS) as previously described in Reiner et al (2012) and values are provided in Tipton et al (accompanying paper). Consumption data obtained from surveys were combined with PFOS contaminant concentrations for corresponding alligator meat samples to determine actual dietary exposure based on the predicted consumption responses (n = 19).…”
Section: Methodsmentioning
confidence: 99%